2021
DOI: 10.1002/smll.202102710
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Cobalt Atom Clusters in CNT‐Wired MoS2 Tube‐in‐Tube Nanostructures with Enhanced Sulfur Immobilization and Catalyzation for Li–S Batteries

Abstract: cathodes, fast capacity degradation, and low Coulombic efficiency. The low electrical/ionic conductivities of sulfur, shuttle effect of long-chain lithium polysulfides (Li 2 S n , 4 ≦ n ≦ 8) and large volume expansion of sulfur cathode (80%) upon lithiation during charge/discharge hinder the practical application of Li-S batteries. [6][7][8] Various strategies have been implemented to overcome these problems including a) designing novel cathodes to increase the electrode conductivity and inhibiting lithium pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 58 publications
0
43
0
Order By: Relevance
“…[ 25–30 ] Among the tested metal compounds, sulfides such as MoS 2 , VS 2 , CoS 2 , Ni 3 S 2 , and Sb 2 S 3 , have demonstrated particularly strong sulfiphilic ability toward LiPS trapping and low lithiation voltages. [ 31–36 ] However, cathodes based on metal sulfides are generally characterized by moderate electrical conductivities, limited sulfur utilization, insufficient cycling stability, and low rate capabilities. [ 37–41 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 25–30 ] Among the tested metal compounds, sulfides such as MoS 2 , VS 2 , CoS 2 , Ni 3 S 2 , and Sb 2 S 3 , have demonstrated particularly strong sulfiphilic ability toward LiPS trapping and low lithiation voltages. [ 31–36 ] However, cathodes based on metal sulfides are generally characterized by moderate electrical conductivities, limited sulfur utilization, insufficient cycling stability, and low rate capabilities. [ 37–41 ]…”
Section: Introductionmentioning
confidence: 99%
“…While the battery assembled with S/TiN NPs@rGO electrode exhibited capacities of 1123, 914, 768, 646, 570, and 483 mAh g −1 , respectively. In addition, the rate performance of S/TiN NFs@rGO electrode was also compared with some reported cathodes based on TiN or some other catalytic materials [ 23,24,39–41 ] (Figure 6g), which demonstrated the excellent properties of S/TiN NFs@rGO electrode. Figure 6h displays the initial discharge capacity of 895 mAh g −1 at 2 C and a capacity retention of 659 mAh g −1 after 200 cycles at 2 C for S/TiN NFs@rGO electrode.…”
Section: Resultsmentioning
confidence: 94%
“…Recently, researchers have found that atomic clusters and nanoparticles exhibited excellent catalytic performance in facilitating the conversion of polysulfides. [121,122] Currently, transition metals are the main choice for such catalysts, which have been shown to significantly improve the electrochemical performance of RT NaS batteries. Thus, Qiao et al developed the transition-metal (Fe, Cu, and Ni) clusters loaded onto hollow carbon nanospheres (HC) as host for sulfur (S@M-HC, where M stands for metal) to improve the performance of RT NaS batteries.…”
Section: Metal Clusters and Particlesmentioning
confidence: 99%
“…Recently, researchers have found that atomic clusters and nanoparticles exhibited excellent catalytic performance in facilitating the conversion of polysulfides. [ 121,122 ]…”
Section: Catalytic Reversible Conversion Of Polysulfidesmentioning
confidence: 99%